2008
DOI: 10.3141/2056-02
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Vertical Illuminance to Pedestrian Visibility in Crosswalks

Abstract: Twenty-six participants evaluated a series of crosswalk lighting designs by visually detecting objects at each crosswalk location while traveling in a moving vehicle. The research was performed on a closed test track under nighttime conditions while the participants were driving an SUV with regular halogen headlamps. The conditions included several vertical illuminance levels (6, 10, 20, and 30 lux), varied luminaire types [high-pressure sodium (HPS) and metal halide (MH)], and various target object types (ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…From the results of this study motion seems to draw more attention than expectancy when it comes to detecting new objects at nighttime on roadways. The results of this study reinforce the safety benefits of overhead lighting (Edwards & Gibbons, 2008;Polus & Katz, 1978;Wanvik, 2009) and decrease in visual performance of older drivers (Owens, Wood, & Owens, 2007;Wood, Tyrrell, & Carberry, 2005). Finally, the results also confirm existing research that drivers tend to detect human form (static or moving) with relative ease when compared to other inanimate objects (Balk, et al, 2008;Johansson, 1973;Owens, et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…From the results of this study motion seems to draw more attention than expectancy when it comes to detecting new objects at nighttime on roadways. The results of this study reinforce the safety benefits of overhead lighting (Edwards & Gibbons, 2008;Polus & Katz, 1978;Wanvik, 2009) and decrease in visual performance of older drivers (Owens, Wood, & Owens, 2007;Wood, Tyrrell, & Carberry, 2005). Finally, the results also confirm existing research that drivers tend to detect human form (static or moving) with relative ease when compared to other inanimate objects (Balk, et al, 2008;Johansson, 1973;Owens, et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
“…Overhead lighting also increases the distance at which pedestrians are detected (Bhagavathula, et al, 2012;Edwards & Gibbons, 2008). Presence of overhead lighting not only decreases the risk of pedestrian accidents (Wanvik, 2009), but also reduces the number of nighttime pedestrian crashes (Pegrum, 1972;Polus & Katz, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…By analysing the number of missed and incorrect detections and the response time to correct detections, it was found that 20 lx additional vertical illuminance was required for satisfactory results. This value was confirmed in a dynamic test with a similar group of elderly persons (Edwards and Gibbons 2008). Of course, the additional vertical illuminance is more effective if the installation supplying it is such that an increase of horizontal lighting level is limited as much as possible.…”
Section: Pedestrian Road Crossingsmentioning
confidence: 60%
“…186 US guidance 4 suggests instead to use vertical illuminances (at 1.5 m height), these being 10 lux and 2 lux for areas of high and medium pedestrian conflict, these data as determined from test track studies. 187 A limitation of specifying a single value of illuminance is that it does not account for local conditions: it may be too low if visual adaptation is raised by extraneous local lighting or by a generally high level of road lighting. In the UK, TR12 of the Institution of Lighting Professionals overcomes this by recommending an illuminance relative to that of the road in which the crossing is placed, which is itself chosen partly with consideration to the surrounding environment.…”
Section: Drivers' Detection Of Pedestriansmentioning
confidence: 99%
“…186 US guidance 4 suggests instead to use vertical illuminances (at 1.5 m height), these being 10 lux and 2 lux for areas of high and medium pedestrian conflict, these data as determined from test track studies. 187…”
Section: Lighting For Pedestriansmentioning
confidence: 99%